Optical sensing and control of T cell signaling pathways - Lee, Hae Nim; Lee, Seung Eun; Inn, Kyung-Soo; Seong, Jihye (Frontiers in Physiology, 2024)
T cells regulate adaptive immune responses through complex signaling pathways mediated by T cell receptor (TCR). The functional domains of the TCR are combined with specific antibodies for the development of chimeric antigen receptor (CAR) T cell therapy. In this review, we first overview current understanding on the T cell signaling pathways as well as traditional methods that have been widely used for the T cell study. These methods, however, are still limited to investigating dynamic molecular events with spatiotemporal resolutions.Therefore, genetically encoded biosensors and optogenetic tools have been developed to study dynamic T cell signaling pathways in live cells. We review these cutting-edge technologies that revealed dynamic and complex molecular mechanisms at each stage of T cell signaling pathways. They have been primarily applied to the study of dynamic molecular events in TCR signaling, however, they will further aid in understanding the mechanisms of CAR activation and function. Therefore, genetically encoded biosensors and optogenetic tools offer powerful tools for enhancing our understanding of signaling mechanisms in T cells and CAR-T cells. ABBREVIATION 39 AP-1 activator protein 1 APC antigen-presenting cell bNLS bipartite nuclear localization signal BRS basic residue-rich sequence CaM Ca 2+ binding protein calmodulin CAR chimeric antigen receptor CD cluster of differentiation CFP cyan fluorescent protein CIB1 cryptochrome-interacting basic-helix-loop-helix cpFP circular permuted fluorescent protein cSMAC central supramolecular activation cluster CRAC channel Ca 2+ release-activated Ca 2+ channel CRY2 cryptochrome 2 CryoEM cryogenic electron microscopy DAG diacylglycerol ddFP dimerization dependent-dependent fluorescent protein dSMAC distal supramolecular activation cluster ER endoplasmic reticulum ERK extracellular signal-regulated kinase FLIM fluorescence lifetime imaging microscopy FLINC fluorescence fluctuation increase by contact FP fluorescent protein FRET fluorescence resonance energy transfer GEF guanine-nucleotide-exchange factor Grb2 growth factor receptor-bound protein 2 hOPN4 human melanopsin IP3 inositol 1,4,5-triphosphate IP3R inositol 1,4,5-triphosphate receptor IRAP insulin responsive aminopeptidase ITAM immunoreceptor tyrosine-based activation motif Itk IL2 Inducible T Cell Kinase KD dissociation constant